High-thermal-conductivity aluminum nitride composite material and preparation method thereof

By adding oxide, boron -containing resin and silicon carbide fiber to the slurry of Aln ceramic, the problem of poor thermal conductivity of Aln ceramic has been solved, the high heating rate and density are improved, and the sintering temperature is reduced.

CN119350039AActive Publication Date: 2025-01-24CHANGZHOU LIANDE CERAMICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411374461.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-24
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The thermal conductivity of existing AlN ceramics is poor and cannot meet the high thermal conductivity requirements.

Method used

By adding yttrium oxide as a sintering aid to the slurry, the amount of yttrium oxide is optimized, and boron-containing resin and silicon carbide fibers are introduced during the sintering process to improve the thermal conductivity of ceramic materials.

Benefits of technology

Significantly improve the thermal conductivity and density of aluminum nitride composite materials, reduce the sintering temperature, and enhance the structural stability and strength of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068349650000111
    Figure BDA0005068349650000111
  • Figure BDA0005068349650000121
    Figure BDA0005068349650000121
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, and particularly discloses a high-thermal-conductivity aluminum nitride composite material and a preparation method thereof. The high-thermal-conductivity aluminum nitride composite material comprises the following substances in parts by weight: 950-960 parts of aluminum nitride; 55 to 65 parts of yttrium oxide; 85 to 95 parts of PVB (Polyvinyl Butyral); 50 to 60 parts of DBP (dibutyl phthalate); 15 to 18 parts of castor oil; 0-10 parts of a reclaimed material; 380 to 400 parts of a solvent; the preparation method comprises the following steps: S1, raw material weighing; S2, defoaming treatment; S3, tape casting; S4, printing molding; the composite material can be used in the field of semiconductors, and has the advantages of high density and high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramics, and more specifically, to a high thermal conductivity aluminum nitride composite material and a preparation method thereof. Background Art

[0002] Commonly used ceramic heat dissipation materials mainly include: Al2O3, BeO, SiC, AlN, etc. Among these ceramic materials, Al2O3 is the most widely used and mature heat dissipation material, but its thermal conductivity is low, so it cannot meet the high thermal conductivity requirements. BeO has good comprehensive properties, but its toxicity limits its application. Although SiC has a high thermal conductivity, its preparation process is complicated, the cost is high, and the dielectric constant is high.

[0003] In comparison, AlN ceramics have excellent thermal conductivity, are non-toxic, and have thermal conductivity similar to that of silicon materials. They are ideal thermal conductive materials and have received extensive attention from academia and industry. With the development of science and technology and industry, the demand for high thermal conductivity special-shaped ceramic parts has increased rapidly. The thermal conductivity of current AlN ceramics still has some shortcomings. Summary of the invention

[0004] In order to improve the problem of poor thermal conductivity of current AlN ceramics, the present application provides a high thermal conductivity aluminum nitride composite material and a preparation method thereof.

[0005] The present application provides a high thermal conductivity aluminum nitride composite material, which adopts the following technical solution:

[0006] In a first aspect, the present application provides a high thermal conductivity aluminum nitride composite material, comprising the following substances in parts by weight: 950-960 parts of aluminum nitride; 55-65 parts of yttrium oxide; 85-95 parts of PVB; 50-60 parts of DBP; 15-18 parts of castor oil; 0-10 parts of recycled material; and 380-400 parts of solvent.

[0007] By adopting the above technical solution, aluminum nitride is a ceramic material with high thermal conductivity, excellent electrical insulation performance, low expansion coefficient, corrosion resistance and wear resistance, and is an excellent semiconductor material. Aluminum nitride relies on phonons for heat transfer. The surface contact between aluminum nitride ceramic grains provides a smooth channel for phonon propagation. The second phase and various defects in the lattice dissipate heat from phonons and thus reduce thermal conductivity. Since oxygen can be dissolved in aluminum nitride to form oxygen defects, oxygen defects scatter phonons and reduce thermal conductivity. Therefore, this application adopts the addition of yttrium oxide as a sintering aid in the slurry. The addition of yttrium oxide can effectively reduce the oxygen content in aluminum nitride, and further carbon thermal reduction reaction occurs, which can effectively improve the thermal conductivity of the ceramic material.

[0008] Optionally, the following substances are included in parts by weight: 950-960 parts of aluminum nitride; 60 parts of yttrium oxide; 85-95 parts of PVB; 50-60 parts of DBP; 15-18 parts of castor oil; 0-10 parts of recycled material; and 380-400 parts of solvent.

[0009] By adopting the above technical solution, the amount of yttrium oxide added in the slurry is optimized, and the preferred amount of yttrium oxide added is 6%, so that the yttrium oxide can remain granular in the slurry and is not easy to adhere, thereby maintaining the surface contact between the aluminum nitride ceramic grains, providing a smooth channel for phonon propagation, thereby further improving the thermal conductivity of the composite material. However, for some conventional aluminum nitride ceramics, after adding yttrium oxide, the yttrium oxide particles are more likely to adhere, thereby reducing the surface contact and channels between the aluminum nitride grains, and reducing the thermal conductivity of the ceramic composite material. In addition, by optimizing the amount of yttrium oxide added, the sintering temperature of the ceramic can be reduced.

[0010] Optionally, 10-20 parts by weight of boron-containing resin is also included.

[0011] By adopting the above technical solution, a boron-containing resin is added to the slurry. The addition of boron can effectively promote the graphitization of the resin, and boron can react with the active functional groups of the resin to convert the small molecular volatile components generated during the resin cracking process into stable components retained in the matrix, which can improve the density and structural stability of the slurry. The introduction of the resin material can wrap and bond the various components in the slurry, and the carbon generated by the resin during the sintering process can undergo a carbon thermal reduction reaction with the oxide layer on the surface of the aluminum nitride particles, effectively reducing or eliminating the oxide layer on the surface of the aluminum nitride, which is beneficial to the phonon transmission between the aluminum nitride particles, thereby stably improving the thermal conductivity of the composite material.

[0012] Optionally, the boron-containing resin includes boron carbide modified phenolic resin, and the mass ratio of the boron carbide to the phenolic resin is 6-7:3-4.

[0013] By adopting the above technical solution, phenolic resin is added to the slurry. During the sintering process, the carbon-carbon bond of the phenolic resin is broken to generate phenol and cresol, and then the methylene reacts with the hydroxyl group to cause a carbon-hydrogen bond, or the hydroxyl functional groups react with each other to form an ether bond. As the temperature rises, further deoxidation and dehydrogenation reactions occur, gradually transforming into a carbon material. The carbon material can undergo a carbon thermal reduction reaction with the oxide layer on the surface of aluminum nitride, reducing or eliminating the oxide layer on the surface of aluminum nitride, thereby promoting the mass transfer of aluminum nitride and improving the density and thermal conductivity of the ceramic. The modification of phenolic resin with boron carbide can achieve carbonization and graphitization of phenolic resin at a lower temperature. During heat treatment, boron carbide can react with the active functional groups of the phenolic resin, and can transform the small molecular volatile components produced by the cracking of the phenolic resin into stable components, thereby improving the density and structural stability of the ceramic.

[0014] Optionally, the boron-containing resin further includes a boron-containing epoxy resin, and the boron-containing epoxy resin includes a boron-containing filler and an epoxy resin.

[0015] By adopting the above technical scheme, the boron-containing filler is used in combination with the epoxy resin, so that the thermal conductivity of the epoxy resin can be effectively improved, and the epoxy resin can also produce in-situ cracked carbon during the cracking process. The cracked carbon can also react with the surface oxide layer of the aluminum nitride to maintain the mass transfer effect between the aluminum nitride grains, and cooperate with the boron-containing phenolic resin to improve the density and thermal conductivity of the ceramic material.

[0016] Optionally, the method for preparing the boron-containing filler comprises the following steps: stirring and mixing sodium chloride, PH-DDM and boron nitride, tabletting, heating and curing, water bath immersion, drying, and crushing to obtain the boron-containing filler.

[0017] By adopting the above technical solution and the sacrificial salt template method, a three-dimensional interconnected network with a honeycomb structure is obtained, and the PH-DDM is carbonized and loaded on the surface of boron nitride by heating and curing, thereby forming a three-dimensional staggered thermal conductive network structure. By modifying the epoxy resin with a boron-containing filler having a thermal conductive network structure, the mass transfer channel of aluminum nitride can be increased, effectively improving the thermal conductivity of the ceramic.

[0018] Optionally, the boron nitride is boron nitride modified with tannic acid.

[0019] By adopting the above technical scheme, boron nitride is modified by tannic acid. Tannic acid has a large number of catechol or triol groups and can participate in non-covalent interactions, such as ion pairing and hydrogen bonding. Therefore, after the boron nitride is modified, the dispersion uniformity of boron nitride in the epoxy resin can be improved, that is, the boron-containing raw material can be evenly dispersed in the slurry, so that the ceramic obtains a uniform thermal conductivity effect.

[0020] Optionally, 3-5 parts of silicon carbide are also included.

[0021] By adopting the above technical solution, silicon carbide fiber has excellent properties such as high strength, high thermal conductivity, superplasticity and superelasticity. After being added to ceramics, the fibers can be used to pull the various components in the ceramics, thereby effectively improving the density and strength of the ceramics.

[0022] In a second aspect, the present application provides a method for preparing a high thermal conductivity aluminum nitride composite material, using the following technical solution:

[0023] A method for preparing a high thermal conductivity aluminum nitride composite material comprises the following steps: S1, weighing raw materials: weighing aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvent by weight, mixing, and ball milling to obtain slurry;

[0024] S2, degassing treatment: using a vacuum pump to degas the slurry;

[0025] S3, tape casting: placing the deaerated slurry on a tape casting machine for tape casting, molding, drying, cutting, and obtaining a molded product;

[0026] S4, printing and molding: printing tungsten paste heating circuit on the molded product, rolling the rod, molding, and obtaining a semi-finished product;

[0027] S5. Sintering and shipment: Place the semi-finished products in containers for sintering, inspection and shipment.

[0028] Optionally, the aluminum nitride is refined aluminum nitride that has been ball-milled for 25-30 hours.

[0029] By adopting the above technical solution, aluminum nitride is ball-milled to refine the grains of aluminum nitride, introduce lattice distortion and introduce an appropriate amount of Fe element, thereby effectively reducing the sintering temperature of aluminum nitride, which is beneficial to the production of ceramics.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. Due to the addition amount of yttrium oxide in the slurry of the present application, the addition amount of yttrium oxide is preferably 6%, so that the yttrium oxide can remain granular in the slurry and is not easy to adhere, thereby maintaining the surface contact between the aluminum nitride ceramic grains, providing a smooth channel for phonon propagation, thereby further improving the thermal conductivity of the composite material. However, for some conventional aluminum nitride ceramics, after adding yttrium oxide, the yttrium oxide particles are more likely to adhere, thereby reducing the surface contact and channels between the aluminum nitride grains, and reducing the thermal conductivity of the ceramic composite material. In addition, by optimizing the addition amount of yttrium oxide, the sintering temperature of the ceramic can be reduced.

[0032] 2. In the present application, preferably phenolic resin is added to the slurry. During the sintering process, the carbon-carbon bond of the phenolic resin is broken to generate phenol and cresol, and then the methylene reacts with the hydroxyl group to cause the carbon-hydrogen bond, or the hydroxyl functional groups react with each other to form an ether bond. As the temperature rises, further deoxidation and dehydrogenation reactions occur, and gradually turn into carbon materials. The carbon material can react with the oxide layer on the surface of aluminum nitride to undergo a carbon thermal reduction reaction, reduce or eliminate the oxide layer on the surface of aluminum nitride, thereby promoting the mass transfer of aluminum nitride and improving the density and thermal conductivity of the ceramic. The modification of phenolic resin by boron carbide can realize the carbonization and graphitization of phenolic resin at a lower temperature. During the heat treatment, boron carbide can react with the active functional groups of the phenolic resin, and can convert the small molecule volatile components produced by the cracking of the phenolic resin into stable components, thereby improving the compactness and structural stability of the ceramic.

[0033] 3. This application adopts the sacrificial salt template method to obtain a three-dimensional interconnected network with a honeycomb structure, and carbonizes PH-DDM and loads it on the surface of boron nitride by heating and curing, thereby forming a three-dimensional staggered thermal conductive network structure. By modifying the epoxy resin with a boron-containing filler having a thermal conductive network structure, the mass transfer channel of aluminum nitride can be increased, effectively improving the thermal conductivity of the ceramic.

[0034] 4. The method of the present application performs ball milling treatment on aluminum nitride, which can refine the grains of aluminum nitride, introduce lattice distortion and introduce an appropriate amount of Fe element, thereby effectively reducing the sintering temperature of aluminum nitride, which is beneficial to the production of ceramics. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the embodiments.

[0036] In the embodiments of the present application, the instruments and equipment used are as follows, but not limited thereto:

[0037] Drugs: The phenolic resin is brand No. 213 produced by Tianjin Daying Resin Co., Ltd. The viscosity of the phenolic resin at 20°C is 0.8-1.53 ​​Pa·s, the solid content is 80±3%, and the active component content is not higher than 21%; the particle size of boron carbide is 2.5-3.5μm, and the purity is 85%; the recycled material is the scraps of aluminum nitride, which can be collected and reused.

[0038] Preparation Example

[0039] Preparation Example 1

[0040] Phenolic resin and boron carbide were mixed at a mass ratio of 7:3 at a speed of 100 r / min to prepare a boron-containing phenolic resin.

[0041] Preparation Example 2

[0042] 0.027 g of tannic acid and 3 g of boron nitride were dispersed in 100 mL of deionized water, ultrasonically dispersed for 30 min, magnetically stirred for 8 h, filtered, washed, and dried at 40° C. to obtain tannic acid-modified boron nitride.

[0043] Preparation Example 3

[0044] Take 0.027g of tannic acid and 3g of boron nitride and disperse them in 100mL of deionized water, ultrasonically disperse them for 30min, and magnetically stir them for 8h. Weigh 0.56g of copper sulfate and dissolve it in 100mL of deionized water to obtain a copper solution. Mix the copper solution with the boron nitride solution to obtain a mixed solution. Use NaOH solution to adjust the pH of the mixed solution to 7.4, and adjust the temperature of the mixed solution to 50℃ and stir for 4h. Filter and separate, wash with water and alcohol three times, and dry at 40℃ for 24h to obtain complex-modified boron nitride.

[0045] Preparation Example 4

[0046] 1.98 g of 4,4-diaminodiphenylmethane, 1.329 of paraformaldehyde and 1.889 of phenol solution were added to 30.0 mL of toluene solution and heated at 80° C. for 5 hours. Then, the mixture was cooled to room temperature and washed three times with 0.1 mol / L sodium hydroxide aqueous solution (30 mL) and deionized water (30 mL) until the pH value was constant at 7.0+1.0, then the solvent was removed by rotary evaporation and then vacuum dried at 50° C. for 24 h to obtain a light yellow granular solid (yield of 83%), named PH-DDM.

[0047] 2g NaCl, 0.15g PH-DDM and 0.30g boron nitride were mixed and stirred, the mixed powder was placed in a tablet press for tableting, and placed at 180°C for curing for 2h to obtain a solidified product, which was repeatedly washed in a 60°C water bath, dried at 80°C, crushed, repeatedly washed in a 60°C water bath again, and dried at 80°C again to obtain a boron-containing filler. The epoxy resin and the boron-containing filler were stirred and mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.

[0048] Preparation Example 5

[0049] 2g NaCl, 0.15g PH-DDM and 0.30g boron nitride prepared in Preparation Example 2 were mixed and stirred, the mixed powder was placed in a tablet press for tableting, and placed at 180°C for curing for 2h to obtain a solidified product, which was repeatedly washed in a 60°C water bath, dried at 80°C, crushed, repeatedly washed in a 60°C water bath again, and dried at 80°C again to obtain a boron-containing filler. The epoxy resin and the boron-containing filler were stirred and mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.

[0050] Preparation Example 6

[0051] 2g NaCl, 0.15g PH-DDM and 0.30g boron nitride prepared in Preparation Example 3 were mixed and stirred, the mixed powder was placed in a tablet press for tableting, and placed at 180°C for curing for 2h to obtain a solidified product, which was repeatedly washed in a 60°C water bath, dried at 80°C, crushed, repeatedly washed in a 60°C water bath again, and dried at 80°C again to obtain a boron-containing filler. The epoxy resin and the boron-containing filler were stirred and mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.

[0052] Preparation Example 7

[0053] Boron phenolic resin and garnet powder were taken in a mass ratio of 7:3 and magnetically stirred for 30 minutes to obtain boron-containing phenolic resin.

[0054] Preparation Example 8

[0055] Weigh 10% SiC nanofibers and place them in a tube furnace. Then, introduce CH4 and N2 and use CVD method to deposit SiC nanofibers. nf The PyC coating layer was deposited on the surface of the SiC nanofibers. The reaction conditions were controlled as follows: temperature was 1100°C, the flow rate ratio of CH4 and N2 was 1:2, the total system pressure was 20 kPa, and the deposition time was 60 min. SiC nanofibers coated with cracked carbon were prepared at a CH4 gas flow rate of 20 mL / min.

[0056] Example

[0057] Examples 1-3

[0058] On the one hand, the present application provides a high thermal conductivity aluminum nitride composite material, comprising aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvents, and the specific quality is shown in Table 1.

[0059] The solvent is ethanol and butanone in equal amounts.

[0060] On the other hand, the present application provides a method for preparing a high-density phosphate-type positive electrode material, comprising the following steps:

[0061] S1. Weighing raw materials: weigh aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvent by weight, mix, and ball mill at 30 r / s for 24 h to obtain slurry;

[0062] S2, degassing treatment: use a vacuum pump to degas the slurry at 0.07 MPa for 30 minutes;

[0063] S3, tape casting: the deaerated slurry is placed on a tape casting machine at a speed of 10 m / min and a tape casting blade height of 1.0 mm for tape casting, molding, drying at 120°C, and cutting to obtain a molded product;

[0064] S4, printing and molding: printing tungsten paste heating circuit on the molded product, rolling the rod, molding, and obtaining a semi-finished product;

[0065] S5. Sintering and shipment: Place the semi-finished product in a container and sinter it at 1830°C for 36 hours, then inspect and ship it.

[0066] Table 1 Slurry composition of Examples 1-3

[0067] Weight / kg Example 1 Example 2 Example 3 Aluminum Nitride 950 955 960 Yttrium Oxide 55 60 65 PVB 85 90 95 DBP 50 55 60 castor oil 15 16.8 18 Recycled materials 0 0 0 Solvents 380 390 400

[0068] Example 4

[0069] The difference from Example 2 is that an equal mass of refined aluminum nitride that has been ball-milled for 30 hours is used to replace the aluminum nitride in Example 2 to prepare the aluminum nitride composite material.

[0070] Example 5

[0071] The difference from Example 2 is that the slurry further includes 15 kg of the boron-containing phenolic resin prepared in Preparation Example 1 to prepare the aluminum nitride composite material.

[0072] Example 6

[0073] The difference from Example 2 is that the slurry further includes 10 kg of the boron-containing phenolic resin prepared in Preparation Example 1 and 5 kg of the boron-containing epoxy resin prepared in Preparation Example 4 to prepare the aluminum nitride composite material.

[0074] Example 7

[0075] The difference from Example 2 is that the slurry further includes 10 kg of the boron-containing phenolic resin prepared in Preparation Example 1 and 5 kg of the boron-containing epoxy resin prepared in Preparation Example 5 to prepare the aluminum nitride composite material.

[0076] Example 8

[0077] The difference from Example 2 is that the slurry further includes 10 kg of the boron-containing phenolic resin prepared in Preparation Example 1 and 5 kg of the boron-containing epoxy resin prepared in Preparation Example 6 to prepare the aluminum nitride composite material.

[0078] Example 9

[0079] The difference from Example 2 is that the slurry further includes 10 kg of the boron-containing phenolic resin prepared in Preparation Example 1 and 5 kg of the boron-containing phenolic resin prepared in Preparation Example 7 to prepare the aluminum nitride composite material.

[0080] Example 10

[0081] The difference from Example 2 is that the slurry further includes 4 kg of silicon carbide fiber to prepare the aluminum nitride composite material.

[0082] Embodiment 11

[0083] The difference from Example 2 is that the slurry further includes 4 kg of silicon carbide fibers prepared in Preparation Example 8 to prepare an aluminum nitride composite material.

[0084] Comparative Example

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 2 is that in this comparative example, yttrium oxide is not added to prepare the aluminum nitride composite material.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 2 is that in this comparative example, the amount of yttrium oxide added is 30 kg to prepare the aluminum nitride composite material.

[0089] Performance testing

[0090] (1) Thermal conductivity test: The thermal conductivity was measured using the transient flat plate heat source method (TPS2500S, HotDisk). Test parameters: The probe output power was 20.60 mW, the test temperature was room temperature, and the machine was preheated for two hours before the test. Two samples of equal size and smooth surface were prepared before the test.

[0091] Prepare three samples on tinplate according to "GB1727-79 General Preparation Method for Paint Film". After the paint film is completely dry, measure it under constant temperature and humidity conditions.

[0092] (2) Density detection: The density of the sintered porcelain body was measured using the Archiamde drainage method.

[0093] Table 2 Performance test

[0094]

[0095]

[0096] Combining the performance test comparison in Table 2, we can find that:

[0097] 1. By comparing Examples 1-3, Example 4 and Comparative Examples 1-2, it can be found that the thermal conductivity and density of the ceramics prepared in Examples 1-4 are improved, which indicates that the amount of yttrium oxide added in the slurry is optimized in the present application, and the preferred amount of yttrium oxide added is 6%, so that the yttrium oxide can remain granular in the slurry and is not easy to adhere, thereby maintaining the surface contact between the aluminum nitride ceramic grains, providing a smooth channel for phonon propagation, thereby further improving the thermal conductivity of the composite material. Ball milling of aluminum nitride can refine the grains of aluminum nitride, introduce lattice distortion and introduce an appropriate amount of Fe element, thereby effectively reducing the sintering temperature of aluminum nitride, which is beneficial to the production of ceramics.

[0098] 2. By comparing Examples 5-6 with Example 2, it can be found that the thermal conductivity and density of the ceramics prepared in Examples 5-6 are improved, which shows that the addition of boron-containing resin in the slurry in the present application can effectively promote the graphitization of the resin, and boron can react with the active functional groups of the resin to convert the small molecular volatile components produced during the resin cracking process into stable components retained in the matrix, which can improve the density and structural stability of the slurry. The introduction of resin materials can wrap and bond the various components in the slurry, and the carbon produced by the resin during the sintering process can undergo a carbon thermal reduction reaction with the oxide layer on the surface of the aluminum nitride particles, effectively reducing or eliminating the oxide layer on the surface of the aluminum nitride, which is beneficial to the phonon transmission between the aluminum nitride particles, thereby stably improving the thermal conductivity of the composite material.

[0099] 3. By comparing Examples 7-8 with Example 2, it can be found that the thermal conductivity and density of the ceramics prepared in Examples 7-8 are improved, which means that tannic acid is used to modify boron nitride in the present application. Tannic acid has a large number of catechol or triol groups, which can participate in non-covalent interactions such as ion pairing and hydrogen bonding. Therefore, after the boron nitride is modified, the dispersion uniformity of boron nitride in the epoxy resin can be improved, that is, the boron-containing raw material can be evenly dispersed in the slurry, so that the ceramic obtains a uniform thermal conductivity effect.

[0100] 4. By comparing Example 9 with Example 2, it can be found that the thermal conductivity and density of the ceramic prepared in Example 9 are improved, which shows that the use of garnet powder to modify the phenolic resin in the present application can improve the strength of the phenolic resin and thus improve the strength of the ceramic.

[0101] 5. By comparing Examples 11-12 with Example 2, it can be found that the thermal conductivity and density of the ceramics prepared in Examples 10-11 are improved, which shows that the silicon carbide fiber in the present application has excellent properties such as high strength, high thermal conductivity, superplasticity and superelasticity. After being added to the ceramic, the fiber can be used to pull the components in the ceramic, thereby effectively improving the density and strength of the ceramic. The use of carbon-coated silicon carbide fibers can further improve the strength and toughness of the silicon carbide fibers, thereby further improving the density and strength of the ceramic.

[0102] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high thermal conductivity aluminum nitride composite material, characterized in that: The following materials are included in parts by weight: 950-960 parts of aluminum nitride; 55-65 parts of yttrium oxide; PVB 85-95 parts; DBP 50-60 parts; 15-18 parts of castor oil; Recycled material 0-10 parts; 380-400 parts of solvent.

2. The high thermal conductivity aluminum nitride composite material according to claim 1, characterized in that: The following materials are included in parts by weight: 950-960 parts of aluminum nitride; 60 parts of yttrium oxide; PVB 85-95 parts; DBP 50-60 parts; 15-18 parts of castor oil; Recycled material 0-10 parts; 380-400 parts of solvent.

3. The high thermal conductivity aluminum nitride composite material according to claim 2, characterized in that: Also included is 10-20 parts by weight of a boron-containing resin.

4. The high thermal conductivity aluminum nitride composite material according to claim 3, characterized in that: The boron-containing resin includes boron carbide modified phenolic resin, and the mass ratio of the boron carbide to the phenolic resin is 6-7:3-4.

5. The high thermal conductivity aluminum nitride composite material according to claim 4, characterized in that: The boron-containing resin also includes a boron-containing epoxy resin, and the boron-containing epoxy resin includes a boron-containing filler and an epoxy resin.

6. The high thermal conductivity aluminum nitride composite material according to claim 5, characterized in that: The preparation method of the boron-containing filler comprises the following steps: mixing sodium chloride, PH-DDM and boron nitride, tabletting, heating and curing, water bath immersion, drying and crushing to obtain the boron-containing filler.

7. The high thermal conductivity aluminum nitride composite material according to claim 6, characterized in that: The boron nitride is boron nitride modified by tannic acid.

8. The high thermal conductivity aluminum nitride composite material according to claim 2, characterized in that: Also included is 3-5 parts of silicon carbide.

9. A method for preparing a high thermal conductivity aluminum nitride composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weighing raw materials: weigh aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvent by weight, mix, and ball-mill to obtain slurry; S2, degassing treatment: using a vacuum pump to degas the slurry; S3, tape casting: placing the deaerated slurry on a tape casting machine for tape casting, molding, drying, cutting, and obtaining a molded product; S4, printing and molding: printing tungsten paste heating circuit on the molded product, rolling the rod, molding, and obtaining a semi-finished product; S5. Sintering and shipment: Place the semi-finished products in containers for sintering, inspection and shipment.

10. The method for preparing a high thermal conductivity aluminum nitride composite material according to claim 9, characterized in that: The aluminum nitride is refined aluminum nitride that has been ball-milled for 25-30 hours.

Citation Information

Patent Citations

  • Aluminum nitride ceramic composite material and preparation method thereof

    CN104402480A

  • Preparation method of aluminum nitride ceramic substrate with high thermal conductivity for high power microelectronic devices

    CN106431419A

  • Preparation method of high thermal conductivity and high strength aluminum nitride ceramics

    CN108863393A

  • In-phase toughened aluminum nitride ceramic and preparation method thereof

    CN118619695A

  • Method of manufacture of aluminium nitride-based heat-conducting ceramics

    RU2144010C1